Role of eco-innovation and financial globalization on ecological quality in China: A wavelet analysis - Zhang, Huiwen; Khan, Khatib Ahmad; Eweade, Babatunde Sunday; Adebayo, Tomiwa Sunday (Sage Publications Ltd, 2025)
Today, pressing environmental concerns such as addressing climate change and countering global warming have taken center stage among policymakers and diverse organizations. The 2016 Paris Agreement underscores the urgency of decarbonization and the criticality of reducing CO2 emissions for fostering sustainable development. Given that environmental policies can yield diverse impacts across short-, medium-, and long-term periods, it becomes pivotal for policymakers to grasp the underlying causes of ecological footprint by scrutinizing their effects across these different timeframes and periods. Consequently, our investigation delved into the correlation and lead/lag interrelationship between ecological footprint, financial globalization, urbanization, eco-innovation, and economic growth in China spanning from 1985q1 to 2022q4. Leveraging on series of wavelet tools, our study aimed at formulating precise policies. The economic perspective derived from the wavelet analysis indicated a negative correlation between urbanization and eco-innovation with the ecological footprint, whereas economic growth and financial globalization exhibited a positive correlation with the ecological footprint. Consequently, we advocate for the implementation of appropriate policy measures to ensure that the Chinese economy charts a course toward sustainability.
Keywords: Ecological footprint; financial globalization; urbanization; eco-innovation; economic growth